1997
DOI: 10.1126/science.275.5299.515
|View full text |Cite
|
Sign up to set email alerts
|

An Fe 2 IV O 2 Diamond Core Structure for the Key Intermediate Q of Methane Monooxygenase

Abstract: A new paradigm for oxygen activation is required for enzymes such as methane monooxygenase (MMO), for which catalysis depends on a nonheme diiron center instead of the more familiar Fe-porphyrin cofactor. On the basis of precedents from synthetic diiron complexes, a high-valent Fe2(micro-O)2 diamond core has been proposed as the key oxidizing species for MMO and other nonheme diiron enzymes such as ribonucleotide reductase and fatty acid desaturase. The presence of a single short Fe-O bond (1.77 angstroms) per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
588
7
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 578 publications
(646 citation statements)
references
References 29 publications
44
588
7
6
Order By: Relevance
“…A detailed analysis of EXAFS and Mössbauer spectroscopic data revealed that Q is best described as a strongly exchange-coupled S = 2 diiron(IV) species with an Fe-Fe distance of 2.46 Å and pairs of short and long Fe-O bonds of 1.77 and 2.05 Å, respectively, consistent with an Fe 2 IV (µ-O) 2 -diamond core structure 70 . Xue et al 71 (Fig.…”
Section: Dinuclear Bis(µ-oxo)diiron(iv) Model Complexesmentioning
confidence: 99%
“…A detailed analysis of EXAFS and Mössbauer spectroscopic data revealed that Q is best described as a strongly exchange-coupled S = 2 diiron(IV) species with an Fe-Fe distance of 2.46 Å and pairs of short and long Fe-O bonds of 1.77 and 2.05 Å, respectively, consistent with an Fe 2 IV (µ-O) 2 -diamond core structure 70 . Xue et al 71 (Fig.…”
Section: Dinuclear Bis(µ-oxo)diiron(iv) Model Complexesmentioning
confidence: 99%
“…P and Q have been trapped, allowing the oxidation state of their diiron cluster and their overall structure ( Figure 10) to be studied using spectroscopic approaches. 29,32,35 Each has an optical chromophore that allows their reaction with substrates to be monitored.…”
Section: Kinetic Approaches To the Identification Of Intermediatesmentioning
confidence: 99%
“…These intermediates range from the proposed peroxo-bridged compound P, which may require an Fe-Fe distance of up to 4 8, (Kim & Lippard, 1996), to the proposed diamond core bridged compound Q, in which the Fe-Fe distance is 2.47 8, (Shu et al, 1996b).…”
Section: Superposition Of the Two Protomers Of Mmoh Bath Found In Itsmentioning
confidence: 99%